(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2021)
Based on contributions from the sociology of science in the field of Science Education, this article aims to explore and elucidate the concept of fields, formulated by Pierre Bourdieu, in the objects of study of this area. This theoretical study is structured in three parts, which are articulated throughout the text: a synthesis of the general and invariable principles of fields; an elaboration of an analogy between the different field theories (sociology and physics); a discussion about the appropriation of field theories in research studies on Science Education that use them. We discuss the field as a social space, the agents’ habitus, the positions in the field, disputes and interests, distribution of the specific capital, limits, boundaries, and the field autonomy. An interpretation of this complex Bourdieusian concept was defended, in a way to determine the limits of the field and their agents, based on how research has appropriated it. Therefore, a theoretical framework was advanced, coming up with the possible and effective articulations between Science Education and Bourdieu’ Sociology of Science.